2015
DOI: 10.12776/ams.v21i1.539
|View full text |Cite
|
Sign up to set email alerts
|

An Upper Bound Analysis of T-Shaped Equal Channel Angular Pressing

Abstract: T-shaped equal channel angular pressing (T-shaped ECAP) is a novel process of severe plastic deformation (SPD). The maximum effective strain per pass in the T-shaped ECAP is larger than that in the ECAP. Deformation models of the T-shaped ECAP have been proposed by a designed grids deformation experiment considering the deformation dead zone (DDZ) formation or without it. Based on the deformation models, an upper bound approach has been used to analyse the T-shaped ECAP process. The effects of the plastic defo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
2
0
2
Order By: Relevance
“… the angular speed of two working rolls are different; this can be achieved by different rolls diameters at the same speed rotations Under these conditions, the material is submitted to an extra shear deformation in addition to compression deformation. With increased shear deformation as well as the compression, it has been suggested that high angle boundaries develop with increasing strain, and ultrafine grains are formed by continuous recrystallization [13][14][15]. Deformation at cryogenic temperature has emerged as a potential route to develop ultrafine grained (UFG) material with improved mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“… the angular speed of two working rolls are different; this can be achieved by different rolls diameters at the same speed rotations Under these conditions, the material is submitted to an extra shear deformation in addition to compression deformation. With increased shear deformation as well as the compression, it has been suggested that high angle boundaries develop with increasing strain, and ultrafine grains are formed by continuous recrystallization [13][14][15]. Deformation at cryogenic temperature has emerged as a potential route to develop ultrafine grained (UFG) material with improved mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Diantaranya ada yang menggunakan SKD11, Orvar, dan HSS, selebihnya tidak disebutkan dalam jurnal penelitian yang mereka tulis. Kebanyakan penelitian itu lebih terfokus pada hasil perbaikan sifat mekanis material dibanding mengurai secara terperinci kondisi ECAP yang mereka lakukan (Furuno et al 2004;Komura et al 2001;Kuswarini 2012;Lee 2000;Wei et al 2015). Dengan informasi yang terbatas itu, menjadikan kesulitan bagi peneliti penerus yang hendak mengulang atau mengembangkan proses ECAP.…”
Section: Pendahuluanunclassified
“…Didapat bahwa beban kritis plunger hanya berada di 13.7 ton. Dari data ini jelas bahwa kekuatan plunger di bawah gaya upper bound, sehingga menyebabkan plunger gagal sebelum ECAP terlaksanakan (Wei et al 2015).…”
Section: Hasil Dan Pembahasanunclassified
“…In the early 21st century, research observations were focused on bulk non-ferrous metals and their alloys with UFG structure [7][8][9][10][11][12][13]. The review paper [14] is mostly aimed at the analyze of UFG metals and alloys through the DSC method.…”
Section: Introductionmentioning
confidence: 99%